Influence of antiretroviral therapy on bone metabolism of patients with chronic hepatitis B: a review - Dessordi, Renata [UNESP]; Santana, Rodrigo de Carvalho; Navarro, Anderson Marliere [UNESP] (Soc Brasileira Medicina Tropical, 2019)
Hepatitis B is a major public health problem worldwide and associated with significant mortality. To prevent or delay the deleterious effects of chronic infection by the hepatitis B virus, patients should be carefully followed, and antiviral therapy indicated according to specific recommendations. Currently, available drugs inhibit viral replication and slow or stop the progression of inflammation and fibrosis of the liver. However, the drugs for oral use in the treatment of hepatitis B. jointly referred to as nucleoside/nucleotide analogs, are indicated for prolonged use and have potential side effects. The reduction in bone mineral density was associated with the use of tenofovir, already evaluated in patients infected with HIV because the drug is also part of the therapeutic arsenal for this viral infection. There are few studies on the effects of tenofovir in patients with mono hepatitis B. Therefore, this literature review proposes to examine how hepatitis B acts in the body and the mechanisms by which antiretroviral drugs (especially tenofovir) can affect bone metabolism.
Keywords: Tenofovir; Hepatitis B; Bone metabolism; Bone health